A survey of perception towards tax evasion as a crime - Abdul Jabbar, Hijattulah; Abdul Manaf, Nor Aziah (Universiti Utara Malaysia, 2006)
This paper analyzes the perception of Malaysian citizens on the severity of tax evasion relative to other crimes and violations.Perception of tax evasion may somewhat explain the degree of non-compliance with the tax laws. Using data from a mail questionnaire survey, the results of mean and comparative analysis results show that tax evasion items were ranked as the five least serious crimes of 32 listed crimes.Tax evasions is categorised after drugs related offence, violent crimes and commercial crimes.The results also indicate significant differences on perception of tax evasion among ethnic groups, academic qualifications and employment sectors.Our results should be useful to policy makers in Malaysia and elsewhere, as we find an alarming signal that tax evasion is relatively ranked as the least serious offence which could lead to an environment where taxpayers may not be afraid of cheating on their tax returns.